Does Social Status Affect the Politeness Strategies? (Politeness Analysis in Sefeo English Community Podcasts) - Fadillah As Syaufi; Andang Saehu; Otong Setiawan Djuharie (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
SEFEO is an abbreviation of one of the most influential English communities in Indonesia, Share English for Everything Community which was established in 2012 by Zelky Yusuf as the founder and runs until now. SEFEO has a different system for running routine English activities including the figures commonly called SEFEO stars consisting of international students and students who have extraordinary appeal in terms of appearance, popularity in their daily lives, and English language skills. This study, in addition to intending to explain theoretically the existence of elements of politeness theory in conversations in one of the SEFEO English community podcasts. The researcher tries to find the possibility of social factors occurring in the SEFEO English community. Politeness strategies consist of a few principles including off-record, positive politeness, negative politeness, and bald on record According to Brown and Levinson (1978). The researcher chose a qualitative content analysis research method. The researcher took a sample of a podcast entitled "Passion" which was narrated by Robin and Jack and a sample of a podcast entitled “Our Experiences in Learning English” which was narrated by Zelky Yusuf (the owner) and Zulfani. The researcher managed to find a relationship between politeness strategies and a person's social status in the community, including in the podcast entitled "Passion" hosted by Robin and Jack. It turns out that the interaction between the two did not show a significant gap because their status was equally respected in society Meanwhile, the interaction between the president directly and the members who are considered ordinary in the podcast entitled "Our Experiences in Learning English" shows a politeness phenomenon where because of the indication of closeness between the two, the result is that their interaction process is very casual and does not significantly show the gap between the two because one has a higher position in the community environment.